تطوير المواد التعليمية للغة العربية القانونية القائمة على النصوص في كلية الشريعة - Rosmiati; Fuji Astuti (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
Arabic holds a strategic position in Islamic education, particularly in exploring both classical and contemporary Islamic legal sources. However, Arabic language instruction at Islamic universities continues to face challenges regarding the alignment of teaching materials with students’ specific academic needs. This study aims to develop authentic text-based legal Arabic teaching materials by implementing the Arabic for Specific Purposes (ASP) approach for students at the Faculty of Sharia. The research employed the Research and Development (R&D) method, adapting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects involved 71 students from the Islamic Criminal Law, Islamic Economic Law, and Islamic Family Law study programs. The results revealed that the developed authentic legal text-based materials significantly enhanced students' mastery of legal terminology and Arabic reading proficiency, with a notable increase from 22.5% to 70%. This research concludes that integrating authentic legal texts within the ASP framework effectively optimizes Arabic language learning outcomes at the Faculty of Sharia.